2005
DOI: 10.1128/jcm.43.3.1294-1300.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Macrolide-Resistant Streptococcus pneumoniae Isolates in Europe

Abstract: In many European countries, the level of pneumococcal resistance to macrolides has now passed the level of resistance to penicillin G. A total of 82 erythromycin A-resistant isolates of Streptococcus pneumoniae were collected by 11 laboratories in seven European countries. All of the isolates were tested for antimicrobial susceptibility, analyzed for clonal relatedness by multilocus sequence typing, and characterized for macrolide resistance genotypes. The prevalence of the macrolide resistance genotypes varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
41
2
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 35 publications
6
41
2
4
Order By: Relevance
“…Currently, fluoroquinolone resistance in respiratory pathogens is low, but there are strong links between rates of consumption and resistance. 5 Significant relationships between increased fluoroquinolone use and reduced percentage susceptibility have also been demonstrated for a group of 11 bacterial pathogens (P  0.05). 6 The studies for the new fluoroquinolone, moxifloxacin, have demonstrated that mutations in the target genes require more than one mutation.…”
Section: Discussionmentioning
confidence: 96%
“…Currently, fluoroquinolone resistance in respiratory pathogens is low, but there are strong links between rates of consumption and resistance. 5 Significant relationships between increased fluoroquinolone use and reduced percentage susceptibility have also been demonstrated for a group of 11 bacterial pathogens (P  0.05). 6 The studies for the new fluoroquinolone, moxifloxacin, have demonstrated that mutations in the target genes require more than one mutation.…”
Section: Discussionmentioning
confidence: 96%
“…El fenotipo más frecuentemente identificado fue el cMLS, similar a los resultados del estudio realizado en Colombia en el año 2004 (10) y a los análisis hechos en Francia, España, Suiza y Polonia (21,27), mientras que en otros países, como Grecia, Alemania, Chile y un estudio reciente publicado en Argentina, el fenotipo M es el más importante (5,25,28,29).…”
Section: Discussionunclassified
“…Для пневмококков такими фак-торами служат возраст пациента старше 65 лет, терапия β-лактамами в течение последних 3 мес, алкоголизм, им-муносупрессия (включая терапию глюкокортикостерои-дами -ГКС), наличие нескольких сопутствующих забо-леваний [7]. В настоящее время устойчивые к макролидам и пенициллинам стрептококки встречаются в Европе примерно в 30% случаев [8], в России -в 5,6% [9].…”
Section: контактная информацияunclassified
“…Другой путь связан с приобретением генов mef, коди-рующих зависимые от ATФ белки, активно выводящие антибиотики из бактериальной клетки. Наличие генов mef приводит к слабой устойчивости к макролидам, и микро-организм остается чувствительным к клиндамицину [14]. При этом резервуаром генетических детерминант устой-чивости считаются непатогенные S. mitis и S. oralis.…”
Section: контактная информацияunclassified